Understanding and supporting pricing decisions using multicriteria decision analysis: an application to antique silver in South Africa - Stephens, Jed (Department of Statistical Sciences, 2021)
This dissertation presents an application of multicriteria decision analysis to understand and support pricing decisions in fields where goods are unique and described by their characteristics. The specific application area of this research is antique silver objects, where a complete iteration of the multicritia decision process is performed. This includes two problem structurings using SODA which provide rich detail into this application area. Multi-attribute additive models are constructed, with attribute partial value functions elicited using different methods: directly (bisection methods), indirectly (MACBETH and linear interpolation) and with discrete choice experiments. The applicability and advantages of each method is discussed. Additionally, an open source R package to implement the design of discrete choice experiments is created. The multi-attribute models provide key insights into decision maker's reasoning for price; and contrasting different decision maker's models explains the market. A risk adverse relationship between multicriteria model score and price is characterised and various inverse utility functions investigated. Two decision support systems are fully developed to address the needs of Cape silver decision makers in South Africa.